2019
DOI: 10.1016/j.foodchem.2018.11.113
|View full text |Cite
|
Sign up to set email alerts
|

Oat and lipolysis: Food matrix effect

Abstract: Oat is rich in a wide range of phytochemicals with various physico-chemical, colloidal and interfacial properties. These characteristics are likely to influence human lipid metabolism and the subsequent effect on health following oat consumption. The aim of this work was to investigate the impact of oat materials varying in complexity on the lipolysis process. The composition, structure and digestibility of different lipid systems (emulsions, oil bodies and oil enriched in phytosterols) were determined. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“… ( A ) FFA released over time from WPI-stabilized emulsion in respect to two different forms of BS: NaTC and NaDC at 10mM under physiological conditions at 310.15 K. Experimental results of CMC of NaTC and NaDC at 310.15 K with errors are also shown. The CMC of NaTC and NaDC have been shown to be statistically significant, p < 0.0001, and are comparable to previously determined values (5–20% of FFA after 60 min for NaTC and NaTDC at 10 mM and 50 mM, methylcellulose stabilized emulsion [ 64 ], 10–13% of FFA after 60 min for mix BS at 9.7 mM, WPI-stabilized emulsion [ 65 ], 6.5–15% of FFA after 60 min. for mix BS at 10 mM [ 66 ].…”
Section: Figuresupporting
confidence: 87%
“… ( A ) FFA released over time from WPI-stabilized emulsion in respect to two different forms of BS: NaTC and NaDC at 10mM under physiological conditions at 310.15 K. Experimental results of CMC of NaTC and NaDC at 310.15 K with errors are also shown. The CMC of NaTC and NaDC have been shown to be statistically significant, p < 0.0001, and are comparable to previously determined values (5–20% of FFA after 60 min for NaTC and NaTDC at 10 mM and 50 mM, methylcellulose stabilized emulsion [ 64 ], 10–13% of FFA after 60 min for mix BS at 9.7 mM, WPI-stabilized emulsion [ 65 ], 6.5–15% of FFA after 60 min. for mix BS at 10 mM [ 66 ].…”
Section: Figuresupporting
confidence: 87%
“…In vitro digestion studies have shown that the gastrointestinal fate and digestibility of oil bodies under simulated GIT conditions depend on their biological origin. For instance, oil bodies isolated from oats have been shown to be relatively resistant to digestion, which was attributed to their tendency to strongly aggregate under gastrointestinal conditions, the resistance of their interfacial coatings to enzyme hydrolysis, and the presence of minor components that interfered with the digestion process (such as phytosterols and fibers; Wilde, Garcia‐Llatas, Lagarda, Haslam, & Grundy, ). Conversely, the oil bodies isolated from almonds have been shown to be more digestible under simulated GIT conditions (Gallier & Singh, ).…”
Section: Gastrointestinal Fatementioning
confidence: 99%
“…Thus, as recently stated by Corsten et al, hindering adsorption of BS is one of the main approaches to control lipolysis [131]. A recent work by Wilde et al also highlights the importance of food structure, apart from composition, in digestibility of oat-based food matrices [132]. The presence of phytosterols affected the stability and physical-chemical properties of mixed micelles promoting the disappearance of the smaller micelles following digestion.…”
Section: Interfacial Approaches To Studying Lipolysis: Emulsion Studiesmentioning
confidence: 93%